Optimal and responsible use of antibiotics. Issue 5 (October 2019) - Depuydt, Pieter; De Waele, Jan J.
Abstract : Purpose of review: In this review, we focus on the dual face of antibiotic therapy in the critically ill that must harmonize the need for early, appropriate and adequate antibiotic therapy in the individual-infected patient with the obligation to limit antibiotic selection pressure as much as possible to preserve its future potential. Recent findings: Recent articles have highlighted and detailed the various aspects, which determine antibiotic efficacy, and have identified adjunctive treatments, such as source control, which impact outcome. In addition, settings and indications where antibiotics do not improve outcome and may cause harm have been identified. Summary: Reconciling antibiotic efficacy with the limitations of their use is feasible but requires a dedicated and sustained effort throughout the whole process of clinical decision-making, from initial suspicion of sepsis to its definitive treatment.